Theology of Sin in the Torah and Its Implications. A Lesson for Ecohumanism - Bello, Oluwaniyi Samuel (Corpus Intellectual, 2025)
The concept of sin is universal and peculiar to humanity. Sin is the act of breaking either divine or societal laws that are meant to restrict the evil acts of humanity. Different approaches have been documented on the concept of sin as an expression of evil. Attention is focused on this direction because Nigeria (being the scope of the study) is a multi- religious nation, where Godly messages, prayers, and all other religious activities are taking place daily against sin and its consequences, yet the level of atrocities such as; human ritual, kidnapping for ransom, massive killing, rape, fraud, incendiarism and looting of nation’s treasury among others is gaining more appresciative ground. Data is sourced from the relevant scholarly literature. The findings revealed that people hardly consider ill-human behaviour ridiculous but rather a classic way of exposure and pleasure. These seems to have brought havoc to the land. The work suggested that strict observation and practice of the tenet spelled out in the Torah would create a better environment.